Essentials of Pathophysiology for Nursing Practice - Cook, Neal; Cook, Neal; Shepherd, Andrea; Boore, Jennifer (SAGE Publications, 2019)
A straight-forward, detailed overview of pathophysiology, providing nursing students with clear and simple explanations of the basic principles that underpin health and illness, and the main causes of disease. The book uses person-centred nursing as its guiding principle (in-line with the new NMC standards) to encourage students to develop a more detailed understanding of specific disorders and learn how to apply the bioscience theory to nursing practice and patient care. Key features: Full-colour diagrams and figures: all content supported by colourful, reader-friendly illustrations. Person-centred bioscience: a fictional family woven through the book encourages students to think holistically about pathophysiology and consider the lived-experiences of different conditions and diseases. Online resources: access to online materials for lecturers and students, including multiple choice questions, videos, flashcards, lecturer test bank, an image bank and a media teaching guide.